Erythropoietin concentrations and isoforms in urine of anonymous Olympic athletes during the Nagano Olympic Games - Berglund, B.; Wide, L. (Scandinavian Journal of Medicine & Science in Sports, 2002)
The ordinary doping control urine samples of 36 anonymous participants (cross-country skiers, biathlon athletes, and curling athletes) of the 1998 Nagano Olympic Games were analyzed for erythropoietin and erythropoietin isoforms. The urine erythropoietin concentration (IU/l) was determined with a competitive radioimmunoassay method and the isoforms were studied by electrophoresis and given as milli albumin mobility units (mAMU). Erythropoietin was detectable in 23 out of 36 specimens (64%). The biathlon and curling athletes had similar urine concentration of erythropoietin. The group of 16 cross-country skiers had significantly (P < 0.05) increased urine concentration of erythropoietin as compared to curling athletes and four of them had urine erythropoietin concentrations between 3.6 and 5.1 IU/l. The electrophoretic mobility of erythropoietin was determined in all eight samples with urine concentration of erythropoietin of more than 2 (range 2.1-5.1) IU/l. No single urine specimen with a median erythropoietin electrophoretic mobility below the cut-off level of 670 mAMU (indicative of doping with recombinant erythropoietin) was registered. Erythropoietin in urine was detected in 71% and the isoforms of Epo characterized in 29% of the anonymous Olympic endurance athletes. The urine concentration of erythropoietin in the biathlon and curling athletes were similar to those of non-athletes. The group of cross-country skiers had higher levels of erythropoietin in urine. These higher levels of urine erythropoietin in cross-country skiers are partly due to more concentrated urine specimens.